THE INFLUENCE OF COMPENSATION ON THE MOTIVATION AND PERFORMANCE OF MSMEs EMPLOYEES IN THE PRODUCTION OF SANAN TEMPEH CHIPS - Sri Wahyuni; Djoko Koestiono; Agustina Shinta Hartati Wahyuningtyas (Socio-Economics/Agribusiness Department, 2022)
The study aims to determine the influence of compensation on motivation and employee performance in the MSMEs production of sanan tempeh chips. This research is a type of explanatory research. The research method quantitatively uses Structural Equation Modeling (SEM) analysis with the Warp Partial Least Square (WarpPLS) approach. Primary data were obtained through in-depth interviews using questionnaires, and field observations while secondary data were obtained through literature studies from various related sources. Selected 60 samples with simple random sampling technique as respondents in this study. The results showed that compensation had a positive and significant effect on motivation. Compensation also has a positive and significant effect on employee performance. Then motivation has a positive and significant influence on employee performance.